Model development of innovative wood substitutes for the sustainable growth of the Thai wood substitution industry - Tawee Anuntaruttana; Taweesak Roopsing (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The continuously occurring problems of forest depletion have resulted in the deforestation of countries and climate change. In order to resolve this problem, the development of innovative wood substitutes is essential. This research strives to develop a model for innovative wood substitutes for the sustainable growth of the Thai wood substitution industry. Qualitative and quantitative studies were employed to collect data through interviews and questionnaires. The subjects in this study included 500 entrepreneurs from the timber, lumber, and wood substitution industries. The results showed that the model for innovative wood substitutes for the sustainable growth of the Thai wood substitution industry consists of four main components, i.e., (1) customer orientation; (2) innovation and technology; (3) research and development; and (4) resources. The focus group results revealed that the developed structural equation model simulation passed the criteria of the data model fit evaluation with a chi-squared probability level (p) of 0.274, CMIN/DF = 1.071, goodness of fit index (GFI) = 0.969, and root mean square error of approximation (RMSEA) = 0.012.
Keywords: 650; industry; innovative; structural equation model; sustainable; wood substitute